2012
DOI: 10.1364/oe.20.021196
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of transient stimulated Brillouin scattering in optical fibers seeded with phase-modulated light

Abstract: Beam combining of phase-modulated kilowatt fiber amplifiers has generated considerable interest recently. We describe in the time domain how stimulated Brillouin scattering (SBS) is generated in an optical fiber under phase-modulated laser conditions, and we analyze different phase modulation techniques. The temporal and spatial evolutions of the acoustic phonon, laser, and Stokes fields are determined by solving the coupled three-wave interaction system. Numerical accuracy is verified through agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 12 publications
1
80
0
Order By: Relevance
“…The resulting tones of the phase modulator were spaced by 66.6 MHz; which is ~1.5x greater than the BG FWHM of the primary response. Zeringue et al argue in [9] that optimal SBS suppression for a given phase-broadened bandwidth is when the spacing of the phase modulator tones are 2-3 times greater than the BG FWHM. The bit pattern in this study is not optimal, but it will be shown that the PRBS scheme sufficiently suppressed SBS.…”
Section: Frequency (Ghz)mentioning
confidence: 99%
“…The resulting tones of the phase modulator were spaced by 66.6 MHz; which is ~1.5x greater than the BG FWHM of the primary response. Zeringue et al argue in [9] that optimal SBS suppression for a given phase-broadened bandwidth is when the spacing of the phase modulator tones are 2-3 times greater than the BG FWHM. The bit pattern in this study is not optimal, but it will be shown that the PRBS scheme sufficiently suppressed SBS.…”
Section: Frequency (Ghz)mentioning
confidence: 99%
“…Equations (1)-(3) have been used to describe Brillouin scattering in a passive fiber without amplification [6] and with a nominal 10× gain [7]. To simulate an amplifier with realistic gain and gain saturation, (4) and (5) are included.…”
Section: Numerical Modelmentioning
confidence: 99%
“…With the modulation period set at much shorter times than the acoustic phonon lifetime or the light traverse time, large SBS suppression factors can be obtained. 5 Typically, white noise source 3 (WNS) and pseudorandom bit sequence 6,7 (PRBS) have been the prevalent phase modulation techniques for kW-class fiber amplifiers. Recently, in a direct comparison conducted at the kW-level in Yb-doped amplifiers, PRBS phase modulation was shown to provide superior SBS suppression to that provided by WNS.…”
Section: Introductionmentioning
confidence: 99%